2021
DOI: 10.3390/su13126628
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Distributed Planning with Asymmetric Information. A Technological Driver for Sustainable Development

Abstract: The growing interest in sustainable development is reflected in both the market’s sensitivity to environmental and social issues and companies’ interest in the opportunities that sustainable development objectives provide. SMEs, which account for most of the world’s pollution, have significant resource constraints for a sustainable development. Sharing their scarce resources can help them to overcome these constraints and to gain agility and organisational resilience against uncertainties, but the distrust inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…For redesigning the supply chain, the supply chain managers must consider the following factors: supply chain base strategy, supply chain understanding and design principles for supply chain resilience based on strategy assessment of the trade-off between efficiency and redundancy. Rius-Sorolla et al. (2021) defined agility as responding rapidly to unpredictable situations.…”
Section: Analysis Of Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…For redesigning the supply chain, the supply chain managers must consider the following factors: supply chain base strategy, supply chain understanding and design principles for supply chain resilience based on strategy assessment of the trade-off between efficiency and redundancy. Rius-Sorolla et al. (2021) defined agility as responding rapidly to unpredictable situations.…”
Section: Analysis Of Papersmentioning
confidence: 99%
“…(2021) added another principle, knowledge management, to the principles proposed by Christopher and Peck (2004). Rius-Sorolla et al. (2021) observed that organisational characteristics and behaviour are the major drivers for building a resilient supply chain.…”
Section: Analysis Of Papersmentioning
confidence: 99%
“…While sustainability in large business organizations has been widely discussed in the literature in recent years [73] the same does not seem to be true for SMEs. Compared with large companies, small companies are constrained by a lack of resources to invest in technology or human resource capacity to anticipate ecological impact [74,75] or operation resources [76]. Obstacles that prevent SMEs from developing environmentally friendly include limited financial resources, the type of organizational structure and limited training on environmental issues [15,[77][78][79][80].…”
Section: Measuring Sustainabilitymentioning
confidence: 99%